2015
DOI: 10.1007/s10552-015-0700-7
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and weight change in relation to triple-negative breast cancer survival

Abstract: Background To evaluate the influence of body mass index (BMI), weight change on triple-negative breast cancer (TNBC) prognosis in a population-based prospective cohort study. Material and Methods The current analysis included 518 participants diagnosed with TNBC in Shanghai Breast Cancer Survival Study. Weight at 1-year prior to cancer diagnosis, at diagnosis and at 6-, 18- and 36-month after cancer diagnosis and height at 6-month after cancer diagnosis were assessed. Disease-free survival (DFS) and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 37 publications
2
39
0
6
Order By: Relevance
“…None of these provided evidence that weight loss improved survival for overweight and obese cancer survivors; rather, four studies found that weight loss was associated with increased mortality, and the fifth found no significant association with mortality. Similar results were observed in an additional study that examined weight loss and mortality in breast cancer survivors with a BMI ≥24 (and therefore did not meet our inclusion criteria), which reported a significantly higher risk of mortality with weight loss [62]. To help contextualise these findings, we also looked at the results for non-overweight cancer survivors where they were reported in the included studies.…”
Section: Discussionsupporting
confidence: 65%
“…None of these provided evidence that weight loss improved survival for overweight and obese cancer survivors; rather, four studies found that weight loss was associated with increased mortality, and the fifth found no significant association with mortality. Similar results were observed in an additional study that examined weight loss and mortality in breast cancer survivors with a BMI ≥24 (and therefore did not meet our inclusion criteria), which reported a significantly higher risk of mortality with weight loss [62]. To help contextualise these findings, we also looked at the results for non-overweight cancer survivors where they were reported in the included studies.…”
Section: Discussionsupporting
confidence: 65%
“…It is also apparent that fluctuations in BMI may similarly influence the prognosis of cancer patients. In instances of triple-negative breast cancer, patients considered obese (BMI ≥28.0 kg/m 2 ) before diagnosis or those achieving weight loss of ≥5% at 18 or 36 months post-diagnosis displayed greater risk of overall mortality, disease recurrence, and disease-specific mortality (30). In patients with early-stage breast cancer, instituting a low-fat diet has resulted in weight reduction and a comparatively lower recurrence rate (31).…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study of a total of 172 TNBC cases observed that WHR was more significantly associated with the risk of TNBC compared with other subtypes (22). A prospective cohort study of 518 TNBC patients reported that WHR was higher among obese TNBC patients (23). The significant negative effects of increased WHR on the risk of basal-like breast cancer were observed among both pre-and postmenopausal women, except those with the luminal A subtype (22).…”
Section: Waist-to-hip Ratio (Whr)mentioning
confidence: 95%